Cerebral venous thrombosis causing posterior fossa lesions: description of a case series and assessment of safety of anticoagulation. - Sousa, D (2016)
BACKGROUND: Isolated posterior fossa parenchymal lesions associated with cerebral venous thrombosis (CVT) are rare. Posterior fossa lesions are an independent predictor of death in CVT. We aim to describe the characteristics and outcome of patients with CVT and isolated posterior fossa lesions and assess the safety of anticoagulation in patients with posterior fossa lesions associated with CVT. METHODS: We retrieved data from all patients with posterior fossa parenchymal lesions in the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) cohort related to clinical features, therapy and outcome. Fisher's exact test was used to evaluate associations. To assess the safety of anticoagulation in CVT patients with posterior fossa lesions we considered all patients with a lesion in this topography, either isolated or with concomitant supratentorial lesions, and compared the rate of new intracranial haemorrhages on repeated imaging with the remaining cohort. RESULTS: Out of 624 patients, 12 had isolated posterior fossa lesions and 14 had posterior fossa lesion with accompanying supratentorial lesions. The lateral sinus was most frequently occluded (n = 11). Involvement of the superior sagittal sinus was significantly less frequent compared to the remaining patients of the cohort (p = 0.013). None of the patients with isolated posterior fossa lesion died but 3 remained dependent on follow-up. Poor outcome (modified Rankin Scale ≥3) was more frequent in patients with any posterior fossa lesion, even when on anticoagulation (29.2% vs. 11.9%; OR 3.04; 95% CI 1.2-7.6; p = 0.018). Of the 24 anticoagulated patients with a posterior fossa lesion, 3 (12.5%) had new haemorrhages on repeated imaging, compared with 30 out of 495 anticoagulated patients (6.1%) without posterior fossa lesions (p = 0.19). CONCLUSIONS: We describe the largest series of CVT patients with associated posterior fossa lesions. When compared to anticoagulated CVT patients without posterior fossa lesions, CVT patients with posterior fossa lesions on full anticoagulation did not have a significant increase in the rate of new intracranial haemorrhages.